Implementasi Augmented Reality Pada Pengenalan Tanaman Herbal Berbasis Android - Muladi, Muhammad Hasyim; Listyorini, Tri; Supriyati, Endang (Yayasan Literasi Sains Indonesia, 2022)
Technological developments produce a variety of new products, such as augmented reality, which can combine the real world with virtual images. One of them is that it can be used as an educational medium. An example is introducing types of herbal plants by displaying 3D images. This is done to help people recognize the types of herbal plants and their benefits. This application was created with the aim of educating the public about the types of herbal plants. The application is made based on Android which was developed using the Multimedia Development Life Cycle (MDLC) method.